Psychometric of Triple Elimination Knowledge Questionnaire for Healthcare Workers: A Pilot Study: Psychometric evaluation 3E Questionnaire - Raya, Reynie Purnama; Wilandika, Angga; Rahmilasari, Giari; Holizah, Santi Nur (IAKMI South Tangerang Branch, 2025)
Background: The Triple Elimination Programme aims to reduce mother-to-child transmission of HIV, syphilis, and hepatitis B, making the assessment of health workers’ knowledge about these infections essential for monitoring its success. Objective: This study evaluates the psychometric properties of the Triple Elimination Knowledge Questionnaire using Classical Test Theory and Structural Equation Modeling to ensure reliability and validity. Methods: A 42-person cross-sectional study was conducted. The analysis included item difficulty, internal consistency, concept validity, and reliability. Factor loadings, AVE, CR, Cronbach's alpha, and rho-A coefficients assessed construct validity. The HTMT assessed discriminant validity. Structural equation modelling tested predictive linkages among knowledge domains. Results: Item difficulty varied widely, and most corrected item–total correlations exceeded 0.30. KR-20 coefficients ranged from 0.661 to 0.733, with an overall reliability of 0.848. Construct validity was generally supported, though some domains had AVE < 0.50. CR values exceeded 0.70, confirming internal consistency. HTMT values below 0.90 indicated discriminant validity. Structural modelling revealed that triple-elimination knowledge significantly predicted HIV, syphilis, and hepatitis knowledge domains (β = 0.613–0.805, p < 0.001). Conclusion: The questionnaire demonstrated strong reliability and validity, suggesting its usefulness for assessing healthcare workers’ knowledge in the triple elimination programme.